ANALYSIS OF BUSINESS MODEL CANVAS (BMC) AS A BUSINESS STRATEGY AT WIN PRODUCTION WEDDING ORGANIZER IN BANDAR LAMPUNG CITY - Idham Sedayu Mahera; Dora Rinova (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The creative service industry, particularly wedding organizer services, has experienced significant growth in Indonesia due to changing lifestyles, increasing consumer expectations, and rising demand for professionally managed wedding events. This study aims to analyze the Business Model Canvas (BMC) as a business strategy at Win Production Wedding Organizer in Bandar Lampung City. The Business Model Canvas, introduced by Osterwalder and Pigneur (2010), is used as a strategic framework to examine nine key business elements: customer segments, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure. This research employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation involving business owners, employees, and customers. Data validity was ensured using triangulation techniques. The findings indicate that Win Production targets middle and upper-middle income couples as its primary customer segment and offers integrated, professional, and flexible wedding services tailored to client needs. The business model demonstrates strong alignment across all nine BMC components, contributing to enhanced competitiveness and business sustainability. The study confirms that Business Model Canvas is an effective strategic tool for analyzing and improving business models in service-based industries, particularly wedding organizer businesses operating in competitive local markets.